Coming Out Asperger : Diagnosis, Disclosure and Self-Confidence. - Murray, Dinah (Jessica Kingsley Publishers, 2005)
Coming Out Asperger explores the complexity of diagnosis for Asperger Syndrome, the drawbacks and benefits of disclosing a diagnosis of a ''hidden disability, '' and how this impinges on self-esteem. The contributors include some of the best-known and most exciting writers in the field of Asperger Syndrome (AS) today, and include individuals on the autism spectrum, parents and professionals. The broad range of the chapters, which draw on anecdotal, professional and research-based evidence, make this book a comprehensive and highly original consideration of the implications of an AS diagnosis. T.